Islamophobia in Indonesia - Devi Rizki Apriliani; Rifki Rosyad (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss Islamophobia in Indonesia. The research method is a qualitative type through literature study, by applying content analysis. This study discusses the notion of Islamophobia, historical traces of Islamophobia in the world, and Islamophobia in Indonesia. This research concludes that Islamophobia in Indonesia is born from a public misunderstanding of Islamic concepts that are actually not harmful. The recommendations of this study are for other researchers and community leaders and Muslims, in general, to give a good impression of Islam to the wider community to minimize misunderstandings that can trigger Islamophobia.